2003
DOI: 10.1074/jbc.m212671200
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of T Cell Antigen Receptor-mediated Crk-L-C3G Signaling and Cell Adhesion by Cbl-b

Abstract: Engagement of the T cell antigen receptor (TCR)1 by the antigenic peptide plus major histocompatibility complex (MHC) in the antigen presenting cells triggers rapid tyrosine phosphorylation and activation of protein-tyrosine kinases, the Src family (Lck and Fyn), and the Syk family (Zap-70). Activation of these kinases in turn induces tyrosine phosphorylation of a number of intracellular substrates including adaptor proteins to form intermolecular network (1, 2). Cbl is one of the adaptor proteins, which consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 29 publications
4
57
2
Order By: Relevance
“…Previous work has shown that CRK proteins signal through the RAP1 GEF C3G to regulate RAP1 activation (4,13,14,28). We now show that this pathway is important for chemokineinduced T cell adhesion and migration.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous work has shown that CRK proteins signal through the RAP1 GEF C3G to regulate RAP1 activation (4,13,14,28). We now show that this pathway is important for chemokineinduced T cell adhesion and migration.…”
Section: Discussionsupporting
confidence: 65%
“…This was somewhat surprising, since CRK proteins have previously been implicated in TCR signaling (13,28), and since we observed decreased adhesion in response to anti-TCR stimulation in CRK/CRKL-deficient T cells ( Figure 1 0 3 0 jci.org Volume 125 Number 3 March 2015…”
Section: Methodsmentioning
confidence: 84%
“…Cbl-b-dependent ubiquitylation of CrK-L prevents its association with C3G, therefore, inhibiting CrkL/C3G-driven clustering of cell adhesion molecules, in particular LFA-1 [39]. In accordance with early studies showing Cbl-b upregulation in anergized T cells, Cbl-b À/À T cells are resistant to ionomycin-induced anergy [34,40].…”
Section: Physiological and Molecular Roles Of E3 Ligases In T-cell Tosupporting
confidence: 73%
“…This results in the inhibition of Akt and PKCy-mediated NFkB activation [37], and additionally, prevents Vav1-mediated cytoskeleton rearrangements required for receptor clustering and synapse formation [38]. Furthermore, Cbl-b has been reported to destabilize the immune synapse by interfering with the CrkL/C3G signaling pathway [39].…”
Section: Physiological and Molecular Roles Of E3 Ligases In T-cell Tomentioning
confidence: 99%
“…Conversely, we found that in BMMC, the absence of Cbl-b did not inhibit Ag-induced Fc⑀RI internalization, nor did it have an effect on receptor degradation after 6-h Ag stimulation (data not shown). Furthermore, in WT mast cells, 6-h Ag incubation resulted in even a slight increase in Cbl-b protein expression (data not shown) similar to that observed after TCR stimulation of primary T cells (42). Fc⑀RI stimulation induces the ubiquitination of Syk (43).…”
Section: Discussionmentioning
confidence: 54%